Analisis Penanganan Kehilangan Bagasi Penumpang dan Bagasi Tidak Bertuan Garuda Indonesia Oleh Ground Handling PT Gapura Angkasa di Bandar Udara Juanda Surabaya - Sherina Kumala Dewi (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Garuda Indonesia collaborates with companies engaged in Ground Handling to handle problems faced by passengers including baggage problems. This research aims to identify and explain the system for handling lost passenger baggage and unclaimed baggage by Garuda Indonesia and how to reduce it by Ground Handling PT Gapura Angkasa. The method in this research is descriptive qualitative by means of structured interviews with baggage service unit officers and make observation at the baggage service unit office at Juanda Airport Surabaya on 12 August-23 August 2021 and documentation of field work. In analyzing the data, the researcher went through several stages,that is data reduction, data presentation, and conclusions. The results of the data analysis that the researcher has carried out show that the baggage loss handling system, the officer will search for 14 days from the reporting date and the baggage handling officer will identify the ownership of the baggage. The responsibility of PT. Garuda Indonesia is guided by PM Number 77 of 2011 and on WI (Work Instructions) to reduce the occurrence of baggage loss and unclaimed baggage, namely, passengers are advised to provide a special/special identity on the baggage, check-in counters always provide baggage tag stock, make-up area must always be bright so as to reduce the occurrence of baggage irregularities Passengers always remember their luggage. Keywords: Garuda Indonesia, Baggage Service Unit, Baggage Handling Procedures, Missing Baggage, On Hand Baggage.